KONSISTENSI TERJEMAHAN KATA AWLIYĀ’ DALAM “AL-QUR’AN DAN TERJEMAHANNYA EDISI PENYEMPURNAAN 2019 KEMENAG RI” - Lilah, Qoirul (AL ITQAN: Jurnal Studi Al-Qur'an, 2022)
This research examines the consistency of awliya' word translation in the "Al-Qur'an and its Translations 2019 Improved Edition of the Indonesian Ministry of Religion". This study aims to determine the consistency of awliya' word translation. Consistency means translating the same word as much as possible/thoroughly while still mentioning the context of the verse. This is due to the consistency of awliya' word translation which is meant to show the awliya' context in verse. If the context of the verse is the same, the possibility of translation is the same. The sample in this study is the six verses containing the pronunciation awliya' word with translated as "loyal friend." The six verses are Al-Baqarah: 175, Al-Nisa': 89, Al-Nisa': 144, Al-Ma'idah: 51, Al-Mā'idah: 57 and Al-Mumtahanah: 1. This research categorized as library research, which uses literature. The literature used in this study is in the form of descriptive data and uses the theory of siyaq, asbab nuzul, and consistency to find out the verse's context and the awliya translation's. The analytical result of this study is, that of the six verses in the same context, awliya' is translated as "loyal friend". This shows that there is consistency in translation.